Pelatihan Kewirausahaan dan penyusunan Laporan Sederhana Bagi Pelaku UMKM di Desa Dalung Kabupaten Badung - Ni Wayan Dian Irmayani; Ni Wayan Purnami Rusadi; Ni Luh Mayadi; I Gusti Agung Ayu Intan Fatmayoni; Desak Made Indah paramitha Sari; Ni Made Ari Divayani (CV. Ulil Albab Corp, 2023)
The purpose of this study was to determine the role of motivation and financial management in entrepreneurship for Micro, Small and Medium Enterprises (MSMEs) in Dalung Village, Badung district. Unemployment is a macroeconomic problem that directly affects humans and is one of the most serious problems. The increase in the number of unemployed in Badung district has soared since the Covid-19 pandemic. Entrepreneurship is seen as one way to reduce unemployment. In Dalung Village, Badung district, efforts to form Micro, Small and Medium Enterprises (MSMEs) are still very minimal. Therefore, encouragement and understanding of motivation and financial management are needed to support interest in entrepreneurship. The material presented was about Entrepreneurship Training and Preparation of Financial Reporting for Micro, Small and Medium Enterprises (MSMEs) in Dalung Village, Badung Regency. The participants were all Micro, Small and Medium Enterprises (MSMEs) in Dalung Village, Badung Regency. There are 30 participants who are willing to take part in this training. The importance of training on entrepreneurship and preparation of financial reporting to support interest in entrepreneurship for the people in Dalung Village, Badung district.